2011
DOI: 10.1093/gerona/glr171
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Continued Institutionalization After Hospitalization in Older Adults

Abstract: Most placements in nursing homes are preceded by a hospitalization followed by discharge to a SNF. Discharge to a SNF is associated with a high risk of subsequent long-term care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
92
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(97 citation statements)
references
References 31 publications
3
92
0
2
Order By: Relevance
“…Increasing age, living alone, cognitive impairment particularly dementia, psychiatric diagnoses, and limited functional performance (activities of daily living and instrumental activities of daily living) have all been shown to strongly predict the need for skilled care in the United States and Europe. [11][12][13][14][15]36,37 These findings uniquely inform clinical decision making as they are derived from the largest non-proprietary longitudinal data set concerning individuals with TBI that is representative of patients receiving inpatient rehabilitation for TBI in the United States. 22,23 While age and pre-injury living status are important to consider when establishing a plan of care on admission to IR, skills for independence improve with recovery, making prediction of outcome for any individual challenging and the discharge planning process dynamic.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing age, living alone, cognitive impairment particularly dementia, psychiatric diagnoses, and limited functional performance (activities of daily living and instrumental activities of daily living) have all been shown to strongly predict the need for skilled care in the United States and Europe. [11][12][13][14][15]36,37 These findings uniquely inform clinical decision making as they are derived from the largest non-proprietary longitudinal data set concerning individuals with TBI that is representative of patients receiving inpatient rehabilitation for TBI in the United States. 22,23 While age and pre-injury living status are important to consider when establishing a plan of care on admission to IR, skills for independence improve with recovery, making prediction of outcome for any individual challenging and the discharge planning process dynamic.…”
Section: Discussionmentioning
confidence: 99%
“…These predictors were usually derived from cohort studies that assessed participants' baseline characteristics and chronic conditions but did not account for more proximal, acute events that often precipitate nursing home placement. Goodwin et al, 4 for example, observed in a large dataset from the United States, that 75% of all nursing home placements were preceded by a previous hospitalization. Some studies analyzed predictors of institutionalization in patients with specific diseases like dementia, hip fracture, or heart failure.…”
mentioning
confidence: 99%
“…At the same time, older people are Anxious to live independently, regardless of chronic complex Conditions such as weakness, dementia and fall hazards. However, independent lifestyles may lead to delays and health assessments due to lack of monitoring, which is Associated with long-term poor health problems [3]. Late Health assessment is a risk factor that is stressed as normal this happens because of the fear of institutionalization Lack of medical evaluation [4].…”
Section: Introductionmentioning
confidence: 99%